Rolling member
Patent Information
- Application Number
- JP2023137069
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-25
- Publication Date
- 2025-03-07
Smart Images

Figure 2025031088000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a rolling member. [Background technology]
[0002] In recent years, there has been a need for electrification of automobiles. Electrification requires batteries. Therefore, when an automobile is electrified, the usable space inside the vehicle is reduced and the weight of the vehicle body increases. In order to increase the usable space inside the vehicle and make the vehicle body lighter, there is a demand for smaller and lighter machines such as compressors and motors used in automobiles.
[0003] Rolling parts such as bearings, gears, and shafts are also required to be smaller and lighter. To achieve this, it is necessary to increase the load, such as the load and rotation speed, applied to the rolling parts. However, an increase in load leads to a decrease in the lifespan of the rolling parts, so it is necessary to make the rolling parts higher in performance than before. For example, rolling parts need to be able to withstand harsh operating conditions such as high load, high temperature, rapid acceleration / deceleration, and high vibration. Under such harsh operating conditions, the rolling parts are prone to damage such as indentation-initiated peeling, hydrogen embrittlement-type peeling, and creep wear. Furthermore, in addition to the above damage, gears and shafts may suffer fatigue failure. If debris from fatigue failure of gears and shafts gets mixed into the lubricating oil, it may induce secondary indentation-initiated peeling of the rolling parts, further expanding the damage. For this reason, rolling parts are required to have high resistance to each of these damages.
[0004] Conventional techniques for increasing the strength of rolling parts include those proposed in JP 2009-7614 A (Patent Document 1), Japanese Patent No. 6735589 A (Patent Document 2), and Japanese Patent No. 6356881 A (Patent Document 3). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2009-7614 A [Patent Document 2] Patent No. 6735589 [Patent Document 3] Patent No. 6356881 Summary of the Invention [Problem to be solved by the invention]
[0006] The techniques disclosed in Patent Documents 1, 2, and 3 are all techniques for increasing the surface strength by surface treatment. However, none of the techniques disclosed in Patent Documents 1, 2, and 3 can address all types of damage, including impression-initiated flaking, hydrogen embrittlement flaking, fatigue fracture, and creep wear.
[0007] The present invention has been made in consideration of the problems of the conventional techniques as described above. More specifically, the present invention aims to provide a rolling member capable of suppressing all damages including impression-initiated flaking, hydrogen embrittlement flaking, fatigue fracture, and creep wear. [Means for solving the problem]
[0008] The rolling member of the present disclosure is a rolling member made of steel having a surface. The rolling member has a surface layer on the surface. The steel contains 0.80% by mass to 1.10% by mass of carbon, 0.15% by mass to 0.50% by mass of silicon, 0.30% by mass to 0.70% by mass of manganese, 1.30% by mass to 1.60% by mass of chromium, 0.10% by mass to 0.50% by mass of molybdenum, and 0.12% by mass to 0.50% by mass of vanadium, with the balance being iron and inevitable impurities. The surface layer contains a solid solution of iron and nitrogen. In a first region of the surface layer, which is 5 μm or less deep from the surface, the compressive residual stress is 80 MPa or more. In a second region of the surface layer, which is 100 μm or less deep from the surface, the average grain size of martensite block grains at a comparative area ratio of 30% is 3.0 μm or less. In the second region, at least one of first precipitates mainly composed of either chromium or vanadium and second precipitates mainly composed of either manganese or silicon are dispersed. The structure in the second region is entirely a structure other than cementite. In the third region, which is a surface layer having a depth of 200 μm or less from the surface, the amount of retained austenite is less than 40% of that in the third region. In the third region, the number density of oxide-based inclusions is 4.0 pieces / mm 2 The number density of sulfide inclusions is 6.0 pieces / mm 2 The following is the result. Effect of the Invention
[0009] According to the rolling contact member of the present disclosure, it is possible to provide a rolling contact member capable of suppressing all damage including impression-initiated flaking, hydrogen embrittlement flaking, fatigue fracture, and creep wear. [Brief description of the drawings]
[0010] [Figure 1] 1 is a cross-sectional view of a rolling bearing 100. FIG. [Diagram 2] 1 is a graph showing the relationship between the distance from a raceway surface of steel constituting a rolling member and the concentrations of carbon and nitrogen. [Diagram 3] 3A to 3C are manufacturing process diagrams of the rolling bearing 100. [Figure 4]FIG. 2 is a side view of test piece 70. [Diagram 5] 2 is a cross-sectional view of a ball screw 200. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The details of the embodiment of the present invention will be described with reference to the drawings. In the following drawings, the same or corresponding parts are given the same reference symbols, and duplicated descriptions will not be repeated. An example of a rolling part according to the embodiment is a rolling bearing 100. In this specification, a rolling part is a part that receives power from another part or transmits power to another part while rolling. Also, in this specification, a rolling member is a component of the rolling part. Therefore, the rolling part according to the embodiment is not limited to the rolling bearing 100.
[0012] (Configuration of rolling bearing 100) The configuration of the rolling bearing 100 will be described below.
[0013] Fig. 1 is a cross-sectional view of a rolling bearing 100. As shown in Fig. 1, the rolling bearing 100 is, for example, a deep groove ball bearing. However, the rolling bearing 100 is not limited to a deep groove ball bearing.
[0014] The rolling bearing 100 has, as rolling members, an inner ring 10, an outer ring 20, multiple rolling elements 30, and a cage 40. The central axis of the inner ring 10 is defined as central axis A. The direction of central axis A is defined as the axial direction. The direction passing through central axis A and perpendicular to central axis A is defined as the radial direction. When viewed along the axial direction, the direction along the circumference centered on central axis A is defined as the circumferential direction.
[0015] The inner ring 10 has a width surface 10a, a width surface 10b, an inner diameter surface 10c, and an outer diameter surface 10d. The width surface 10a, the width surface 10b, the inner diameter surface 10c, and the outer diameter surface 10d are sometimes collectively referred to as the surface of the inner ring 10. The inner ring 10 is annular and extends in the circumferential direction.
[0016] The width surface 10a and the width surface 10b are end surfaces of the inner ring 10 in the axial direction. The width surface 10a faces one side in the axial direction (the right side in FIG. 1). The width surface 10b is the surface opposite the width surface 10a in the axial direction and faces the other side in the axial direction (the left side in FIG. 1).
[0017] The inner diameter surface 10c extends in the circumferential direction. The inner diameter surface 10c faces the central axis A. The outer diameter surface 10d extends in the circumferential direction. The outer diameter surface 10d faces the opposite side to the central axis A. In other words, the outer diameter surface 10d is the opposite surface to the inner diameter surface 10c in the radial direction. One end and the other end in the axial direction of the inner diameter surface 10c are connected to the width surface 10a and the width surface 10b, respectively. One end and the other end in the axial direction of the outer diameter surface 10d are connected to the width surface 10a and the width surface 10b, respectively.
[0018] The outer diameter surface 10d has a raceway surface 10da. The raceway surface 10da is a portion of the outer diameter surface 10d that contacts the rolling elements 30. The outer diameter surface 10d is recessed toward the inner diameter surface 10c at the raceway surface 10da. In a cross-sectional view having a diameter in the circumferential direction, the raceway surface 10da is, for example, partially arc-shaped. The inner diameter surface 10 of the inner ring 10 is fitted onto a shaft 60 (corresponding to the above-mentioned shaft) shown by a dotted line in the figure at the inner diameter surface 10c. The shaft 60 does not constitute the rolling bearing 100.
[0019] The outer ring 20 has a width surface 20a, a width surface 20b, an inner diameter surface 20c, and an outer diameter surface 20d. The width surface 20a, the width surface 20b, the inner diameter surface 20c, and the outer diameter surface 20d are sometimes collectively referred to as the surface of the outer ring 20. The outer ring 20 is annular and extends in the circumferential direction.
[0020] The width surface 20a and the width surface 20b are end surfaces of the outer ring 20 in the axial direction. The width surface 20a faces one side in the axial direction (the right side in FIG. 1). The width surface 20b is the surface opposite the width surface 20a in the axial direction and faces the other side in the axial direction (the left side in FIG. 1).
[0021] The inner diameter surface 20c extends in the circumferential direction. The inner diameter surface 20c faces the central axis A. The outer diameter surface 20d extends in the circumferential direction. The outer diameter surface 20d faces the opposite side to the central axis A. In other words, the outer diameter surface 20d is the opposite surface to the inner diameter surface 20c in the radial direction. One end and the other end in the axial direction of the inner diameter surface 20c are connected to the width surface 20a and the width surface 20b, respectively. One end and the other end in the axial direction of the outer diameter surface 20d are connected to the width surface 20a and the width surface 20b, respectively.
[0022] The inner diameter surface 20c has a raceway surface 20ca. The raceway surface 20ca is a portion of the inner diameter surface 20c that contacts the rolling element 30. The inner diameter surface 20c is recessed toward the outer diameter surface 20d at the raceway surface 20ca. In a cross-sectional view having a diameter in the circumferential direction, the raceway surface 20ca is, for example, partially arc-shaped. The outer diameter surface 20d of the outer ring 20 is fitted into a housing (not shown). The outer ring 20 is disposed radially outside the inner ring 10 so that the inner diameter surface 20c faces the outer diameter surface 10d with a gap therebetween in the radial direction.
[0023] The rolling elements 30 are spherical. The rolling elements 30 are disposed between the raceway surface 10da and the raceway surface 20ca. The surfaces of the rolling elements 30 are in contact with the raceway surface 10da and the raceway surface 20ca. The cage 40 is disposed between the outer diameter surface 10d and the inner diameter surface 20c. The cage 40 holds the rolling elements 30 such that the circumferential interval between two adjacent rolling elements 30 is within a certain range.
[0024] The radial dimension from the inner diameter surface 10c to the outer diameter surface 10d of the inner ring 10, or the radial dimension from the inner diameter surface 20c to the outer diameter surface 20d of the outer ring 20, is defined as the wall thickness D1. The diameter of the circular cross section in the direction perpendicular to the extending direction of the shaft 60 inserted into the inner diameter surface 10c of the inner ring 10 (the radial direction of the rolling bearing 100) is defined as D2. In the rolling bearing 100, the maximum value of D1 is 10 mm or more, and D2 is 20 mm or more. That is, the diameter D3 (not shown) of the inner diameter surface 10c is also 20 mm or more. The diameter D3 is larger than the diameter D2 of the shaft 60 by the amount of the radial gap due to the fit intersection.
[0025] The inner ring 10, the outer ring 20, and the rolling elements 30 are made of steel that has been hardened and tempered. The steel constituting the inner ring 10, the steel constituting the outer ring 20, and the steel constituting the rolling elements 30 have the compositions shown in Table 1. Although the balance in Table 1 is listed as "Fe and unavoidable impurities," if these overlap with aluminum, phosphorus, sulfur, nitrogen, and oxygen in Table 1, they may or may not contain other unavoidable impurities.
[0026] [Table 1]
[0027] Carbon affects the hardness of the steel on the surface of the rolling members (the inner ring 10, the outer ring 20, and the rolling elements 30) after quenching. If the carbon content in the steel is less than 0.80% by mass, it is difficult to ensure sufficient hardness on the surface of the rolling members. If the carbon content in the steel is less than 0.80% by mass, it is necessary to supplement the carbon content on the surface of the rolling members by carburizing or the like, which causes a decrease in production efficiency and an increase in manufacturing costs. On the other hand, if the carbon content in the steel exceeds 1.10% by mass, cracks (quench cracks) may occur during quenching. Therefore, in the composition shown in Table 1, the carbon content is set to 0.80% by mass or more and 1.10% by mass or less. It is more preferable that the carbon content in the steel is 0.90% by mass or more and 1.10% by mass or less.
[0028] Silicon is added to ensure workability before deoxidation and nitriding treatments during steel refining. If the silicon content in the steel is less than 0.15 mass%, the tempering softening resistance is insufficient. As a result, the hardness of the surface of the rolling members may decrease due to tempering after quenching or due to a temperature rise during use of the rolling bearing 100. In this case, the workability when processing the rolling members becomes insufficient.
[0029] If the silicon content in the steel exceeds 0.50% by mass, the steel becomes too hard, and the workability when processing the rolling members is rather reduced. In this case, the material cost of the steel increases. Therefore, in the composition shown in Table 1, the silicon content is set to 0.15% by mass or more and 0.50% by mass or less. Among them, the silicon content in the steel is more preferably 0.20% by mass or more and 0.30% by mass or less.
[0030] Manganese is added to ensure the hardenability and hardness of steel. If the manganese content in steel is less than 0.30 mass%, it is difficult to ensure the hardenability of steel. If the manganese content in steel exceeds 0.70 mass%, the amount of manganese-based nonmetallic inclusions, which are impurities, increases. Therefore, in the composition shown in Table 1, the manganese content is set to 0.30 mass% or more and 0.70 mass% or less. It is more preferable that the manganese content in steel is 0.40 mass% or more and 0.50 mass% or less.
[0031] Chromium is added to ensure the hardenability of steel and to form fine precipitates (nitrides, carbonitrides) during nitriding. If the chromium content in steel is less than 1.30% by mass, it is difficult to ensure the hardenability of steel and to form fine precipitates sufficiently. If the chromium content in steel exceeds 1.60% by mass, the material cost of the steel increases. In addition, if the chromium content in steel exceeds 1.60% by mass, there is a concern that the life will be reduced due to the generation of coarse precipitates. Therefore, in the composition shown in Table 1, the chromium content is set to 1.30% by mass or more and 1.60% by mass or less. It is more preferable that the chromium content in steel is 1.40% by mass or more and 1.60% by mass or less.
[0032] Molybdenum is added to steel to ensure its hardenability and to form fine precipitates during nitriding. Molybdenum has a strong affinity for carbon, so it precipitates in the steel as undissolved carbides during nitriding. These undissolved carbides of molybdenum act as precipitation nuclei during quenching, so molybdenum increases the amount of precipitates after quenching.
[0033] If the molybdenum content in the steel is less than 0.10 mass%, it is difficult to ensure the hardenability of the steel and to form fine precipitates sufficiently. If the molybdenum content in the steel exceeds 0.50 mass%, the material cost of the steel increases. Therefore, in the composition shown in Table 1, the molybdenum content is set to 0.10 mass% or more and 0.50 mass% or less. Among them, the molybdenum content in the steel is more preferably 0.20 mass% or more and 0.30 mass% or less.
[0034] Vanadium is added to ensure the hardenability of steel and to form fine precipitates during nitriding. If the vanadium content in steel is less than 0.12% by mass, it is difficult to ensure the hardenability of steel and to form fine precipitates sufficiently. If the vanadium content in steel exceeds 0.50% by mass, the material cost of the steel increases. Therefore, in the composition shown in Table 1, the vanadium content is set to 0.12% by mass or more and 0.50% by mass or less. It is more preferable that the vanadium content in steel is 0.20% by mass or more and 0.30% by mass or less.
[0035] The inner ring 10, the outer ring 20, and the rolling elements 30 are made of steel that has been hardened and tempered. The steel constituting the inner ring 10, the steel constituting the outer ring 20, and the steel constituting the rolling elements 30 are composed of iron and unavoidable impurities other than the above-mentioned materials. In other words, the above-mentioned steels contain phosphorus, sulfur, nitrogen, and oxygen as unavoidable impurities. However, the steels do not have to contain phosphorus, sulfur, nitrogen, and oxygen.
[0036] The surface of the inner ring 10, the surface of the outer ring 20, and the surface of the rolling element 30 are subjected to nitriding treatment to form a surface layer 50. The surface of the surface layer 50 is the surface of the inner ring 10, the surface of the outer ring 20, or the surface of the rolling element 30. The region of the surface layer 50 that is 5 μm or less away from the surface is defined as the first region. The region of the surface layer 50 that is 100 μm or less away from the surface is defined as the second region. The region of the surface layer 50 that is 200 μm or less away from the surface is defined as the third region. The distance from the surface of the surface layer 50 is measured from any point on the surface along a direction perpendicular to the surface. As described above, the first region is a part of the second and third regions, and the second region is a part of the third region. By performing nitriding treatment, the surface layer 50 contains a solid solution of nitrogen in iron. The solid solution here refers to a state in which nitrogen has penetrated into the lattice of iron.
[0037] In the first region, the compressive residual stress is 80 MPa or more. In particular, it is preferable that the compressive residual stress is 80 MPa or more in the entire first region. It is preferable that the compressive residual stress acting in the circumferential direction in the first region is 80 MPa or more. The residual stress in the first region is measured by X-ray diffraction.
[0038] Alternatively, the nitrogen content in the second region may be 0.2 mass % or more and 0.8 mass % or less. The nitrogen content in the second region is measured using an EPMA (Electron Probe Micro Analyzer).
[0039] The steel constituting the inner ring 10, the steel constituting the outer ring 20, and the steel constituting the rolling elements 30 have martensite block grains in the surface layer portion 50. The difference in crystal orientation between two adjacent martensite block grains at the grain boundary is 15° or more. From another perspective, even if there is a location where the crystal orientation is misaligned, if the difference in crystal orientation is less than 15°, the location is not considered to be a grain boundary of martensite block grains. The grain boundaries of martensite block grains are determined by EBSD (Electron Back Scattered Diffraction) method.
[0040] In the second region, the average grain size of the martensite block grains at a comparative area ratio of 30% is 3.0 μm or less. In the second region, the maximum grain size of the martensite block grains is preferably 5.0 μm or less. The average grain size of the martensite block grains at a comparative area ratio of 30% in the second region and the maximum grain size of the martensite block grains in the second region are measured by the following method.
[0041] First, a cross-sectional observation is performed on a cross section including the second region. At this time, the martensite block grains included in the observation field are identified by the EBSD method. This observation field is an area observed at a magnification of 1500 times. Second, the area of each of the martensite block grains included in the observation field is analyzed from the crystal orientation data obtained by the EBSD method. The square root of the maximum area of each of the martensite block grains included in the observation field divided by π / 4 is the maximum grain size of the martensite block grains in the second region.
[0042] Third, the areas of the martensite block grains included in the observation field are added up in descending order of area. This addition is performed until it reaches 30% of the total area of the martensite block grains included in the observation field. The circle equivalent diameter is calculated for each of the martensite block grains that have been added up. This circle equivalent diameter is the square root of the area of the martensite block grain divided by π / 4. The average circle equivalent diameter of the martensite block grains that have been added up is regarded as the average grain size of the martensite block grains when the comparative area ratio in the second region is 30%.
[0043] The steel constituting the inner ring 10, the steel constituting the outer ring 20, and the steel constituting the rolling element 30 have precipitates dispersed in the surface layer 50, particularly in the second region. The precipitates may be first precipitates mainly composed of either chromium or vanadium. The first precipitates may contain only either chromium or vanadium, or may contain both. Alternatively, the precipitates may be second precipitates mainly composed of either manganese or silicon. The second precipitates may contain only either manganese or silicon, or may contain both. The precipitates dispersed in the steel may be only either the first precipitates or the second precipitates, or may be both. In any case, the precipitates are nitrides or carbonitrides.
[0044] The nitrides mainly composed of chromium (vanadium) are nitrides of chromium (vanadium) or are those in which some of the chromium (vanadium) sites in the nitrides are replaced by alloy elements other than chromium (vanadium). The carbonitrides mainly composed of chromium (vanadium) are those in which some of the carbon sites in the carbides of chromium (vanadium) are replaced by nitrogen. The chromium (vanadium) sites in the carbonitrides mainly composed of chromium (vanadium) may be replaced by alloy elements other than chromium (vanadium). Similarly, the nitrides mainly composed of manganese (silicon) are those in which some of the manganese (silicon) sites in the nitrides are replaced by alloy elements other than manganese (silicon). The carbonitrides mainly composed of manganese (silicon) are those in which some of the carbon sites in the carbides of manganese (silicon) are replaced by nitrogen. The manganese (silicon) sites of the manganese (silicon)-based carbonitride may be substituted with alloy elements other than manganese (silicon).
[0045] In the second region, the maximum grain size of the precipitates is preferably 2.0 μm or less. In the second region, the average area ratio of the precipitates is preferably 2.0% or more. The precipitates here are at least one of the first precipitates and the second precipitates. The average area ratio and maximum grain size of the precipitates in the second region are measured by the following method.
[0046] The average area ratio of precipitates is calculated by acquiring a cross-sectional image of the second region at a magnification of 5000 times using a field emission scanning electron microscope (FE-SEM), binarizing the cross-sectional image, and performing image processing on the binarized cross-sectional image. The cross-sectional images are acquired from three or more fields of view, and the average area ratio is the average value of the area ratios of precipitates obtained from the multiple cross-sectional images.
[0047] The grain size of each precipitate is obtained by obtaining the area of each precipitate using the same method as above and calculating the square root of the value obtained by dividing the area by π / 4. The largest grain size among the obtained grain sizes of the precipitates is determined to be the maximum grain size of the precipitates in the second region.
[0048] In the second region, cementite has disappeared. In other words, the second region does not contain cementite. In other words, the structure in the second region is entirely made up of structures other than cementite. Specifically, the structure in the second region is made up of martensite, retained austenite, first precipitates, and second precipitates. The disappearance of cementite in the steel is confirmed by the absence of a carbon peak due to cementite using an EPMA (Electron Probe Micro Analyzer). This will be explained with reference to FIG. 2.
[0049] FIG. 2 is a graph showing the relationship between the distance from the raceway surface of the steel constituting the rolling member and the concentration of carbon and nitrogen. Referring to FIG. 2, the horizontal axis of the graph shows the distance from the raceway surface of the rolling member such as the inner ring 10 in units of mm. The vertical axis of the graph in FIG. 2 shows the concentration of carbon and nitrogen at each position in units of mass %. From FIG. 2, in particular in the second region where the distance from the raceway surface is 0.1 mm or less, no peak of a sudden increase in carbon concentration appears. From this, it can be seen that cementite containing carbon does not exist in the second region. That is, all of the structures constituting the second region of the surface layer 50 in particular are structures other than cementite. Furthermore, if the region where cementite does not exist is 0.02 mm or less away from the raceway surface, it is possible to sufficiently suppress the decrease in life due to wear. Note that the conditions of the EPMA during the measurement of FIG. 2 were that the acceleration voltage of the electron beam irradiated to the object was 15 kV, and the spot diameter, which is the diameter of the cross section perpendicular to the traveling direction of the electron beam, was 2 μm. Furthermore, the measurement was performed for 1 second every 2 μm. The absence of cementite in the second region increases the number density of the first precipitates or the second precipitates.
[0050] In the third region, the amount of retained austenite is less than 40% of that in the third region. Specifically, the amount of retained austenite in the third region is less than 40% of the total amount of retained austenite and the amount of martensite and other structures other than the retained austenite. The amounts of retained austenite and martensite in the third region are measured by an X-ray analyzer.
[0051] In the third region, the number density of oxide inclusions is 4.0 pieces / mm 2 The number density of sulfide inclusions is 6.0 pieces / mm 2 In particular, the number density of oxide-based inclusions in the entire third region is 4.0 pieces / mm 2 The number density of sulfide inclusions is 6.0 pieces / mm 2 It is preferable that:
[0052] Specifically, oxide inclusions are alumina (Al2O3), silicon oxide (SiO2), calcium oxide (CaO), and magnesium oxide (MgO). In this case, if oxide inclusions are considered to be spherical or elliptical, the longest diameter (major axis) of the inclusions is 2 μm or more and is within 1 mm 2 In the case where multiple inclusions are in contact with each other and exist as a single aggregate, the longest straight line distance connecting both ends of the aggregate is the longest diameter. Similarly, here, the longest straight line distance of sulfide-based inclusions with a long diameter of 2 μm or more within 1 mm 2 The number of hits is set to 6.0 or less. The sulfide-based inclusions are specifically manganese sulfide (MnS).
[0053] The number density of oxide-based inclusions and sulfide-based inclusions is measured by FE-SEM (Field Emission Scanning Electron Microscope) and elemental analysis (EDX: Energy dispersive X-ray spectroscopy). Specifically, FE-SEM and EDX are used to count the number of oxide-based inclusions and sulfide-based inclusions with a major axis of 2 μm or more that are present in an area that is 200 μm or less away from the surface of the rolling component (measured from any point on the surface along a direction perpendicular to the surface). The number of inclusions is divided by the area of the area where the inclusions are observed. This gives the number density of inclusions (pieces / mm 2 ) is required.
[0054] The steel constituting the inner ring 10, the steel constituting the outer ring 20, and the steel constituting the rolling elements 30 have retained austenite in the surface layer 50. The amount of retained austenite after heating at 120°C for 2000 hours is defined as the amount of retained austenite after heating. The amount of retained austenite before heating at 120°C for 2000 hours is defined as the amount of retained austenite before heating.
[0055] In the second region, the amount of retained austenite after heating is preferably 60% or more of the amount of retained austenite before heating. From another perspective, in the second region, the rate of change in the amount of retained austenite before and after heating at 120°C for 2000 hours is preferably 40% or less. In the third region, similar to the second region, the amount of retained austenite after heating may be 60% or more of the amount of retained austenite before heating. From another perspective, in the third region, the rate of change in the amount of retained austenite before and after heating at 120°C for 2000 hours may be 40% or less.
[0056] It is preferable that the rolling member has higher residual stress on all surfaces including the inner ring 10. It is preferable that the grain size of the precipitates in the rolling member is small and the area ratio is high (high number density). It is preferable that the number density of inclusions is lower.
[0057] (Method of manufacturing rolling bearing 100) A method for manufacturing the rolling bearing 100 will now be described.
[0058] Fig. 3 is a manufacturing process diagram of the rolling bearing 100. As shown in Fig. 3, the manufacturing method of the rolling bearing 100 mainly includes a preparation step S1, a nitriding treatment step S2, a decarburization treatment step S3, a quenching step S4, a tempering step S5, a post-treatment step S6, and an assembly step S7. The manufacturing method of the rolling bearing 100 may further include a quenching step separate from the quenching step S4, and may further include a tempering step separate from the tempering step S5.
[0059] In the preparation step S1, a workpiece is prepared. When the inner ring 10 and the outer ring 20 are to be formed, an annular member is prepared as the workpiece, and when the rolling elements 30 are to be formed, a spherical member is prepared. The workpiece is made of steel having the composition shown in Table 1.
[0060] In the nitriding step S2, the surface of the workpiece is subjected to a nitriding treatment by holding the workpiece at a temperature equal to or higher than the A1 transformation point for a predetermined period of time in an atmospheric gas containing a nitrogen source gas (e.g., ammonia gas).
[0061] In parallel with the nitriding process S2, a decarburization process S3 may be performed. Decarburization is a phenomenon in which carbon is lost from the surface of steel. Decarburization is a process in which the carbon activity of the atmospheric gas is reduced to a value at which cementite in the steel disappears, and the steel is heated. For this reason, decarburization is performed when the carbon concentration in the steel is high. If the carbon concentration in the steel is already low, the decarburization process S3 does not need to be performed.
[0062] When the decarburization process S3 is carried out while the nitriding process S2 is being carried out, the enriched gas flow rate is adjusted to adjust the carbon activity of the atmospheric gas.
[0063] In the quenching step S4, the workpiece is quenched. This quenching is performed by holding the workpiece at a temperature equal to or higher than the A1 transformation point for a predetermined time, and then cooling the workpiece to a temperature equal to or lower than the Ms transformation point. The Ms transformation point tends to be lower as the concentration of dissolved nitrogen increases. Therefore, the deeper the workpiece (the part farther from the surface) where the nitrogen concentration is low, the higher the Ms point is, and the expansion associated with the martensitic transformation during quenching occurs first in the deep part of the workpiece. Then, when the martensitic transformation occurs in the surface layer of the workpiece with a high nitrogen concentration as the cooling proceeds, the deep part of the workpiece that has already hardened becomes a resistance to the expansion associated with the martensitic transformation in the surface layer of the workpiece, and the surface layer of the workpiece cannot expand completely, and the lattice spacing is compressed when the workpiece reaches room temperature. Therefore, compressive stress remains in the surface layer of the workpiece. There is a correlation between compressive residual stress and hardness (the higher the hardness, the higher the compressive residual stress), and the larger the area ratio of precipitates, the smaller the grain size of martensite block grains, and the smaller the grain size of prior austenite crystal grains, the higher the hardness. The grain size of martensite block grains and the grain size of prior austenite crystal grains become smaller due to the pinning effect of nitrides and carbonitrides of vanadium and molybdenum. In the tempering step S5, the workpiece is tempered. This tempering is performed by holding the workpiece at a temperature below the A1 transformation point for a predetermined time.
[0064] Between the quenching step S4 and the tempering step S5, either the secondary quenching step or the subzero step may be performed, or both may be performed in this order. However, the secondary quenching step and the subzero step may not be performed. In the secondary quenching step, the workpiece is held at a temperature equal to or higher than the A1 transformation point for a predetermined time. However, in the secondary quenching step, the heating temperature is preferably lower than that in the quenching step S4 described above. The subzero step is a heat treatment performed after the secondary quenching step to transform the retained austenite in the steel into martensite. In the subzero step, the steel is cooled to a temperature lower than room temperature and soaked at that temperature. If no further structural change is required, the secondary quenching step and the subzero step may be omitted.
[0065] In a post-processing step S6, the workpiece is subjected to finishing (grinding and polishing) and cleaning. As a result, the inner ring 10, the outer ring 20, and the rolling elements 30 are formed. In an assembly step S7, the inner ring 10, the outer ring 20, and the rolling elements 30 are assembled together with the cage 40. Through the above steps, the rolling bearing 100 having the structure shown in FIG. 1 is manufactured.
[0066] (Effect of Rolling Bearing 100) In the rolling bearing 100, the inner ring 10, the outer ring 20, and the rolling elements 30 are made of steel having the composition shown in Table 1. The steel having the composition shown in Table 1 has a low content of expensive alloy elements. Therefore, the rolling bearing 100 can reduce the cost of the steel material. The rolling members of this embodiment are based on the alloy composition of SUJ2, which is a type of high carbon chromium bearing steel material described in JIS G 4805, and only small amounts of molybdenum and vanadium are added. This makes it possible to reduce the cost of the steel material while improving the hardenability of the high carbon steel and increasing the stability of the austenite layer. Furthermore, the steel material can be used for the inner ring, which is a thick part having a maximum wall thickness of 10 mm or more and a circular diameter perpendicular to the extension direction of the insertable shaft member of 20 mm or more. Since the steel material does not require carburizing treatment, the cost can be reduced compared to the case of using a steel material that requires carburizing treatment.
[0067] In the rolling bearing 100, the inner ring 10, the outer ring 20, and the rolling elements 30 are formed from steel having the composition shown in Table 1, so that fine precipitates are formed in the steel in the surface layer 50 formed by nitriding. The vicinity of these fine precipitates becomes a hydrogen trapping site, so the amount of hydrogen penetration in the surface layer 50 is reduced. Therefore, in the rolling bearing 100, early flaking due to hydrogen embrittlement is unlikely to occur.
[0068] In the rolling bearing 100, the compressive residual stress in the first region is 80 MPa or more. This compressive residual stress suppresses the formation of indentations on the surfaces of the inner ring 10, the outer ring 20, and the rolling elements 30, and also suppresses the growth of cracks originating from the indentations. This compressive residual stress also improves fatigue strength. In this way, the rolling bearing 100 can improve the spalling life due to hydrogen embrittlement and the surface-origin spalling life, as well as the fatigue strength.
[0069] In the rolling bearing 100 and the rolling members contained therein, in the second region, the average grain size of the martensite block grains at a comparative area ratio of 30% is 3.0 μm or less. In the third region, the amount of retained austenite is less than 40% of that in the third region. This improves the fatigue strength of the steel and stabilizes the dimensions of the steel. As a result, it is possible to provide a rolling member that can suppress all damage caused by impression-initiated flaking, hydrogen embrittlement-induced flaking, fatigue fracture, and creep wear.
[0070] In the rolling bearing 100 and the rolling members contained therein, the number density of oxide-based inclusions in the third region is 4.0 pieces / mm 2 The number density of sulfide inclusions is 6.0 pieces / mm 2 This is less than 1. In other words, the number of large inclusions with a major axis of 2 μm or more per unit area is small. By reducing the number density of large inclusions in this way, the probability of the presence of inclusions that can be the starting point of crack propagation decreases. This makes it possible to suppress fatigue fracture, surface-initiated spalling, and internal-initiated spalling of rolling components. Oxide-based inclusions are prone to become a source of stress concentration for fatigue fracture, so reducing them can suppress fatigue fracture. In addition, oxide-based inclusions and sulfide-based inclusions tend to accumulate hydrogen at the interface with the surroundings, so if their number increases, hydrogen embrittlement (fatigue fracture and crack propagation) is more likely to progress. Reducing the number of oxide-based inclusions and sulfide-based inclusions can suppress hydrogen embrittlement.
[0071] In the rolling bearing 100 and the rolling members contained therein, the structure in the second region is entirely other than cementite. Cementite present at the grain boundaries of the crystals constituting the steel promotes crack propagation at the grain boundaries. Therefore, if the cementite disappears, the crack propagation at the grain boundaries of the crystals constituting the steel can be suppressed. Therefore, fatigue failure of the rolling members can be suppressed. Decarburization increases the solid solution ratio of nitrogen, which contributes greatly to solid solution strengthening, in iron, improving the fatigue strength of the steel. Furthermore, the decarburization process for eliminating cementite causes fine precipitates to precipitate in the steel in the surface layer 50. The vicinity of these fine precipitates becomes a hydrogen trapping site, so the amount of hydrogen penetration in the surface layer 50 decreases. Therefore, in the rolling bearing 100 that has been decarburized, early flaking due to hydrogen embrittlement is less likely to occur. EXAMPLES
[0072] In order to evaluate the spalling life due to hydrogen embrittlement, the spalling life due to indentation, and the fatigue strength of the rolling components according to the embodiment, a wear test, a first rolling fatigue life test, a second rolling fatigue life test, and a rotating bending fatigue test were performed. The steels applied to these tests were Steel 1 or Steel 2, as shown in Table 2. Steel 1 is within the composition range shown in Table 1, and Steel 2 is not within the composition range shown in Table 1. Although not shown in Table 2, the compositions of Steel 1 and Steel 2 are within the composition ranges shown in Table 1 with respect to aluminum, phosphorus, sulfur, nitrogen, and oxygen.
[0073] [Table 2]
[0074] The samples applied to these tests were subjected to the first or second heat treatment. As shown in Table 3, when the first heat treatment is applied (samples 1 and 2), the nitriding step S2, the quenching step S4, and the tempering step S5 are performed. Furthermore, when the first heat treatment is applied, the decarburization step S3 is performed, especially if the carbon content in the steel is high. As a guideline, the decarburization step S3 is performed if the carbon concentration in the area adjacent to the surface is 0.90 mass% or more. When the second heat treatment is applied (sample 3), the quenching step S4 and the tempering step S5 are performed, but the decarburization step S3 is not performed even if the carbon concentration is high.
[0075] [Table 3]
[0076] In the nitriding step S2, the decarburization step S3, and the quenching step S4 of the first heat treatment, the steel was held at 850°C for 6 hours in endothermic converted gas and ammonia gas, and then oil quenched. In the quenching step S4 of the second heat treatment, the steel was held at 850°C for 1 hour in endothermic converted gas, and then oil quenched. In the tempering step S5 of the first and second heat treatments, the steel was held at 180°C for 2 hours. As shown in Table 3, the case where the first heat treatment is applied to the first steel is sample 1, the case where the first heat treatment is applied to the second steel is sample 2, and the case where the second heat treatment is applied to the second steel is sample 3.
[0077] For Sample 1, Sample 2, and Sample 3, the compressive residual stress in the first region, the nitrogen content in the second region, and the average grain size of martensite block grains at a comparative area ratio of 30% in the second region were measured. Furthermore, the area ratio of precipitates to the entire surface area of each sample, the amount of retained austenite in the third region, and the number density of oxide-based inclusions and sulfide-based inclusions in the third region were measured. As a measurement method for the bearing part, at least five measurement points were set at intervals of 72° in the circumferential direction, which was the measurement range in this example.
[0078] Condition 1 is that the composition of the steel is within the range of the composition shown in Table 1. Condition 2 is that the compressive residual stress in the first region is 80 MPa or more. Condition 3 is that the nitrogen content in the second region is 0.2 mass% or more and 0.8 mass% or less. Condition 4 is that the average grain size of martensite block grains at a comparative area ratio of 30% in the second region is 3.0 μm or less. Condition 5 is that the amount of retained austenite in the third region is less than 40%. Condition 6 is that the number density of oxide-based inclusions in the third region is 4.0 pieces / mm 2 The condition 6 is that the number density of sulfide-based inclusions in the third region is 6.0 pieces / mm 2 Condition 7 is that the steel sheet has the following properties: 1) the steel sheet has no cementite; 2) the steel sheet has no cementite;
[0079] As shown in Tables 3 and 4, in Sample 1, all of Conditions 1 to 8 are satisfied. In Sample 2, of Conditions 1 to 8, all except Condition 1 are satisfied, and only Condition 1 is not satisfied. In Sample 3, only Condition 5 is satisfied, and all except Condition 5 are not satisfied.
[0080] A comparison between Sample 2 and Sample 3 shows that by performing the nitriding treatment step S2 and satisfying Condition 3, Condition 2 is satisfied (a compressive residual stress of 80 MPa or more acts on the first region), and precipitates are dispersed in large amounts.
[0081] In addition, a comparison between Sample 1 and Sample 2 shows that by satisfying both Condition 1 and Condition 8, fine precipitates are dispersed in greater numbers, and Condition 4 is naturally satisfied (the martensite block grains are refined in the second region). Condition 1 requires the use of steel within the composition range shown in Table 1, and Condition 8 causes the disappearance of cementite. In particular, in Sample 1, cementite disappears due to the decarburization treatment.
[0082] [Table 4]
[0083] <Wear test> The wear test was performed under the conditions shown in Table 5. The results of the wear test are shown in Table 6. The wear resistance was evaluated by observing the wear marks after the test with a laser microscope and calculating the wear volume. As shown in Table 6, it was found that the wear resistance of Sample 1 is superior to Sample 2 and Sample 3. When the wear resistance of the surface is high, hydrogen penetration from the surface to the surface layer 50 is suppressed, and the occurrence of hydrogen embrittlement is suppressed. Therefore, Sample 1 is less likely to experience early peeling due to hydrogen embrittlement than Sample 2 and Sample 3. However, Sample 2 was significantly superior to at least Sample 3.
[0084] [Table 5]
[0085] [Table 6]
[0086] <First rolling fatigue life test and second rolling fatigue life test> The first rolling fatigue life test was conducted under the conditions shown in Table 7. The second rolling fatigue life test was conducted under the conditions shown in Table 8. That is, the first rolling fatigue life test was conducted to evaluate the resistance to surface-initiated spalling in a foreign matter-containing environment, and the second rolling fatigue life test was conducted to evaluate the resistance to surface-initiated spalling in an indentation-forming environment. In each of the rolling bearings subjected to the first rolling fatigue life test and the second rolling fatigue life test, the raceway was one of Sample 1 to Sample 3, but the rolling elements were made of SUJ2 that had been through-hardened. Table 9 shows the results of the first rolling fatigue life test and the second rolling fatigue life test as relative values based on Sample 3 (Sample 3 was evaluated as 1). As shown in Table 9, in both the first rolling fatigue life test and the second rolling fatigue life test, the L of Sample 1 was 1. 10The lifetime (time to 10 percent cumulative probability of failure) was better than Samples 2 and 3, although Sample 2 was at least significantly better than Sample 3.
[0087] [Table 7]
[0088] [Table 8]
[0089] [Table 9]
[0090] <Rotating bending fatigue test> FIG. 4 is a side view of the test piece 70. The test piece 70 is used for the rotating bending fatigue test. In the rotating bending fatigue test, an Ono-type rotating bending fatigue test in accordance with the JIS standard (JIS Z 2274:1978) was performed. In the rotating bending fatigue test, the rotation speed was set to 3600 revolutions per minute, and the number of repeated stress loads was 10 7 The fatigue life of the specimen 70 was evaluated based on the maximum stress at which the specimen 70 did not break at the stage of reaching the number of cycles. As shown in Table 10, the rotating bending fatigue life of Sample 1 was superior to Sample 2 and Sample 3, except that Sample 2 was at least significantly superior to Sample 3.
[0091] [Table 10]
[0092] <Summary> As described above, Sample 1, which satisfies all of Conditions 1 to 8, was superior in spalling life due to hydrogen embrittlement, surface-initiated spalling life, and fatigue strength compared to Samples 2 and 3, which did not satisfy at least one of Conditions 1 to 8. In addition, the results of the wear test were also superior for Sample 1 to Sample 2, and Sample 2 to Sample 3. This makes it clear that by satisfying all of Conditions 1 to 8, it is possible to provide a rolling member that can suppress all damage, particularly indentation-initiated spalling, hydrogen embrittlement spalling, fatigue fracture, and creep wear. In addition, Samples 1 and 2, which do not have cementite, have superior fatigue strength compared to Sample 3, which does have cementite, making it clear that fatigue fracture can be suppressed by not having cementite. EXAMPLES
[0093] Other rolling fatigue life tests are described below.
[0094] <Sample> As rolling bearing samples, Sample 4, Sample 5, and Sample 6 were prepared. Sample 4, Sample 5, and Sample 6 are single direction thrust ball bearings of JIS standard 51106 type having an inner diameter of 30 mm, an outer diameter of 47 mm, and a width of 11 mm.
[0095] The inner and outer rings of Sample 4 were made of steel having the composition shown in Table 11. The inner and outer rings of Sample 5 and the inner and outer rings of Sample 6 were made of steel having the composition shown in Table 12. The balls of Samples 4, 5 and 6 were made of stainless steel (SUS440C).
[0096] The composition shown in Table 11 is within the range of the composition shown in Table 13 (hereinafter referred to as the "first composition") and the composition shown in Table 14 (hereinafter referred to as the "second composition"). In contrast, the composition shown in Table 12 is within the composition range of SUJ2 defined in the JIS standard, and is outside the range of the first composition in Table 13 and the second composition in Table 14.
[0097] [Table 11]
[0098] [Table 12]
[0099] [Table 13]
[0100] [Table 14]
[0101] The inner and outer rings of Sample 4 and the inner and outer rings of Sample 5 were subjected to a heat treatment process. That is, the inner and outer rings of Samples 4 and 5 were subjected to all of the quenching process (S4), tempering process (S5) and nitriding process (S2) of Fig. 3. The inner and outer rings of Sample 6 were not subjected to a heat treatment process. More specifically, the inner and outer rings of Sample 6 were subjected to the quenching process (S4) and tempering process (S5) of Fig. 3, but were not subjected to the nitriding process (S2) of Fig. 3.
[0102] A rolling fatigue life test was conducted on Sample 4, Sample 5, and Sample 6. As shown in Table 15, the rolling fatigue life test was conducted under the following conditions: maximum contact pressure of 2.3 GPa, rapid acceleration and deceleration between 0 rpm and 2500 rpm, and lubrication with a mixture of polyglycol and pure water.
[0103] As shown in Table 15, L 10When comparing the lifespan (the time when the cumulative failure probability becomes 10 percent), the rolling fatigue life of Sample 5 was longer than that of Sample 6. From these comparison results, it was experimentally demonstrated that the rolling fatigue life can be improved by carrying out nitriding treatment so that the nitrogen content in the surface layer of the rolling components is 0.2 percent by mass or more and 0.8 percent by mass or less.
[0104] As shown in Table 15, L 10 Comparing the lives, the rolling fatigue life of Sample 4 was longer than that of Sample 5. From these comparison results, it was experimentally demonstrated that forming at least one of the inner ring, outer ring, and balls from the steel of the first composition in Table 13 results in fine dispersion of precipitates in the surface layer, thereby improving the rolling fatigue life.
[0105] [Table 15]
[0106] <Hydrogen penetration characteristics> The hydrogen penetration characteristics of the surface layers of the raceway members (inner ring and outer ring) of Sample 4 and Sample 6 were evaluated by the following method. In this evaluation, first, the raceway members of Sample 4 and Sample 6 were heated from room temperature to 400°C before being subjected to the above-mentioned rolling fatigue life test, and the amount of hydrogen released from the raceway members of Sample 4 and Sample 6 before being subjected to the rolling fatigue life test was measured. Second, the raceway members of Sample 4 and Sample 6 after being subjected to the rolling fatigue life test for 50 hours were heated from room temperature to 400°C, and the amount of hydrogen released from the raceway members of Sample 4 and Sample 6 after being subjected to the rolling fatigue life test for 50 hours was measured.
[0107] In Sample 6, the ratio of the amount of hydrogen released before and after the rolling fatigue life test (i.e., the amount of hydrogen released after being subjected to the rolling fatigue life test divided by the amount of hydrogen released before being subjected to the rolling fatigue life test) was 3.2. On the other hand, in Sample 4, the ratio of the amount of hydrogen released before and after the rolling fatigue life test was 1.0. From this comparison, it was experimentally clarified that the formation of a surface layer on the surface suppresses hydrogen penetration into the surface layer, thereby suppressing early flaking due to hydrogen embrittlement.
[0108] (Rolling parts other than the rolling bearing 100) Fig. 5 is a cross-sectional view of the ball screw 200. As shown in Fig. 5, the ball screw 200 has a screw shaft 210, a ball nut 220, a plurality of balls 230, and a seal member 240. The circulation system of the balls 230 in the ball screw 200 is not particularly limited. The circulation system of the balls 230 in the ball screw 200 may be, for example, a tube system, a return tube (pipe) system, a deflector system, an end deflector system, an end cap system, a top system, or the like.
[0109] The screw shaft 210 has an outer peripheral surface 210a. A screw groove 210b is formed on the outer peripheral surface 210a. The ball nut 220 has a hole extending along the direction of the central axis of the screw shaft 210. The inner wall surface of this hole is the inner peripheral surface 220a of the ball nut 220. A screw groove 220b is formed on the inner peripheral surface 220a. The screw shaft 210 is inserted into the ball nut 220 so that the outer peripheral surface 210a faces the inner peripheral surface 220a. The ball 230 is disposed between the screw grooves 210b and 220b. The hole of the ball nut 220 through which the screw shaft 210 passes is closed by a seal member 240. The screw shaft 210 also passes through a hole formed in the seal member 240.
[0110] The screw shaft 210, the ball nut 220, and the balls 230 are made of steel that has been hardened and tempered. The composition of the steel is within the range of the composition shown in Table 1 (the above condition 1 is satisfied). The surfaces of the screw shaft 210, the ball nut 220, and the balls 230 are subjected to nitriding treatment (and decarburization treatment) to form a surface layer 50 similar to that of the rolling bearing 100, and the above conditions 2 to 8 are satisfied.
[0111] The ball screw 200 has improved wear resistance, spalling life due to hydrogen embrittlement, surface-origin spalling life, and fatigue strength on the surfaces of the screw shaft 210, the ball nut 220, and the balls 230, making it possible to increase the load capacity and also reduce the size and weight. The miniaturization of the ball screw 200 also makes it possible to reduce the size of peripheral parts and structural members.
[0112] However, it is sufficient that at least one of the screw shaft 210, the ball nut 220, and the balls 230 satisfies all of the above conditions 1 to 8. From another perspective, it is sufficient that at least one of the screw shaft 210, the ball nut 220, and the balls 230 of the ball screw 200 is the rolling member according to the embodiment.
[0113] By rotating the screw shaft 210 around its central axis, the rotational power of the screw shaft 210 is transmitted to the ball nut 220 via the balls 230, and the ball nut 220 moves along the direction of the central axis of the screw shaft 210. In other words, the ball screw 200 is a device that converts the rotational motion of a motor or the like into linear motion. The ball screw 200 is used in, for example, electric actuators, positioning devices, electric jacks, servo cylinders, electric servo presses, mechanical presses, electric brake devices, transmissions, electric power steering devices, electric injection molding machines, and the like.
[0114] In this way, the rolling parts or rolling members according to the embodiments can be applied to rolling parts and rolling members for any purpose as long as conditions 1 to 8 are satisfied. For example, the rolling parts according to the embodiments may be gears, drive shafts, cam followers, etc.
[0115] (Additional Note) The above embodiment includes the following configurations.
[0116] <Appendix 1> A rolling element made of steel having a surface, A surface layer portion is provided on the surface, The steel contains 0.80% by mass or more and 1.10% by mass or less of carbon, 0.15% by mass or more and 0.50% by mass or less of silicon, 0.30% by mass or more and 0.70% by mass or less of manganese, 1.30% by mass or more and 1.60% by mass or less of chromium, 0.10% by mass or more and 0.50% by mass or less of molybdenum, and 0.12% by mass or more and 0.50% by mass or less of vanadium, with the remainder being iron and unavoidable impurities; The surface layer portion contains a solid solution of iron and nitrogen, In the first region of the surface layer portion, which has a depth from the surface of 5 μm or less, a compressive residual stress is 80 MPa or more, In the second region of the surface layer portion having a depth from the surface of 100 μm or less, the average grain size of martensite block grains at a comparative area ratio of 30% is 3.0 μm or less, In the second region, at least one of first precipitates containing either chromium or vanadium as a main component and second precipitates containing either manganese or silicon as a main component are dispersed as precipitates, The structure in the second region is entirely a structure other than cementite, In a third region of the surface layer portion having a depth from the surface of 200 μm or less, the amount of retained austenite is less than 40% of the third region, In the third region, the number density of oxide-based inclusions is 4.0 pieces / mm 2 The number density of sulfide inclusions is 6.0 pieces / mm 2 A rolling member, which is as follows:
[0117] <Appendix 2> 2. The rolling contact member according to claim 1, wherein in the second region, the maximum grain size of the martensite block grains is 5.0 μm or less.
[0118] <Appendix 3> 3. The rolling member according to claim 1, wherein in the second region, the maximum grain size of the precipitates is 2.0 μm or less, and the average area ratio of the precipitates is 2.0% or more.
[0119] <Appendix 4> 4. The rolling member according to any one of claims 1 to 3, which is an inner ring having a maximum wall thickness of 10 mm or more and a circular diameter perpendicular to the extending direction of an insertable shaft member of 20 mm or more.
[0120] <Appendix 5> A rolling component comprising the rolling member according to any one of claims 1 to 4.
[0121] Although the embodiment of the present disclosure has been described above, the above-mentioned embodiment can be modified in various ways. The scope of the present disclosure is not limited to the above-mentioned embodiment. The scope of the present disclosure is defined by the claims, and is intended to include all modifications within the meaning and scope equivalent to the claims. [Explanation of symbols]
[0122] 10 inner ring, 10a, 10b width surface, 10c inner diameter surface, 10d outer diameter surface, 10da raceway surface, 20 outer ring, 20a, 20b width surface, 20c inner diameter surface, 20ca raceway surface, 20d outer diameter surface, 30 rolling element, 40 cage, 50 surface portion, 60 shaft, 70 test piece, 100 rolling bearing, 200 ball screw, 210 screw shaft, 210a outer peripheral surface, 210b screw groove, 220 ball nut, 220a inner peripheral surface, 220b screw groove, 230 ball, 240 seal member, A central shaft.
Claims
1. A rolling element made of steel having a surface, A surface layer is provided on the surface, The steel contains 0.80% by mass or more and 1.10% by mass or less of carbon, 0.15% by mass or more and 0.50% by mass or less of silicon, 0.30% by mass or more and 0.70% by mass or less of manganese, 1.30% by mass or more and 1.60% by mass or less of chromium, 0.10% by mass or more and 0.50% by mass or less of molybdenum, and 0.12% by mass or more and 0.50% by mass or less of vanadium, with the remainder being iron and unavoidable impurities; The surface layer portion contains a solid solution of iron and nitrogen, In the first region of the surface layer portion having a depth of 5 μm or less from the surface, a compressive residual stress is 80 MPa or more, In the second region of the surface layer portion having a depth from the surface of 100 μm or less, the average grain size of martensite block grains at a comparative area ratio of 30% is 3.0 μm or less, In the second region, at least one of first precipitates containing either chromium or vanadium as a main component and second precipitates containing either manganese or silicon as a main component are dispersed as precipitates, The structure in the second region is entirely a structure other than cementite, In a third region of the surface layer portion having a depth from the surface of 200 μm or less, the amount of retained austenite is less than 40% of the third region, In the third region, the number density of oxide-based inclusions is 4.0 pieces / mm 2 The number density of sulfide-based inclusions is 6.0 pieces / mm 2 A rolling member, which is as follows:
2. The rolling member according to claim 1 , wherein in the second region, the maximum grain size of the martensite block grains is 5.0 μm or less.
3. 2. The rolling member according to claim 1, wherein in said second region, a maximum grain size of said precipitates is 2.0 μm or less, and an average area ratio of said precipitates is 2.0% or more.
4. 3. The rolling member according to claim 1 or 2, which is an inner ring having a maximum wall thickness of 10 mm or more and a circular diameter perpendicular to the extending direction of an insertable shaft member of 20 mm or more.
5. A rolling component comprising the rolling member according to any one of claims 1 to 3.
6. A rolling component comprising the rolling member according to claim 4 .
Citation Information
Patent Citations
Head load mechanism for disk device
JP1988056881A
Rolling member for transmission and rolling bearing for transmission
JP2009007614A
Environmentally resistant bearing steel with excellent manufacturability and hydrogen embrittlement resistance
JP6735589B2